O Ardina de Sapatos Gastos - Bia, Alerto (Fundza, 2022)
Bia, Alerto.-- O Ardina de Sapatos Gastos [Livro]. -- Maputo : Fundza, 2022. -- 82 p.; 21 centímentros.-- ISBN: 978-989-8901-58-3
Keywords: Fiction; Short stories